Assessment of the reproductive performances of native sows in Southern Benin - ADOLIGBE, CAMUS (My University, 2021)
Native sows contribute to a large extent to food security and poverty alleviation in Benin. However, their reproductive performance particularly under extensive systems is poorly characterized. The objective of this study was to fill this knowledge gap by selecting 284 multiparous sows based on hair color and some reproductive parameters. The results showed that native sows of Southern Benin can be clustered into three groups with group 3 showing the best reproductive performances including highest average litter size (LS, 10.31 piglets), live-born piglets (LBP, 10.31 piglets), number of functional teats (10.94), andshorter average farrowing interval (6 mo). The analysis of sows’ performances based on their origin revealed that sows from agro-ecological zone 8 have the highest number of LBP and the lowest age at first mating and first farrowing. The analysis of sows’ performances based on the hair color showed that those with black hair have the largest LS and the highest number of LBP. This study showed that Benin’s native sows have good reproductive ability with enough variation to develop a sustainable pig industry for a better contribution to food security and wealth creation.
Keywords: conservation; farrowing interval; litter size; selection